The Effect of Shear and Lap Arrangement on Reinforcement Lap Strength. (November 2017) - Micallef, Marianna; Vollum, Robert
Abstract: The paper is concerned with the design of tension laps in reinforced concrete structures. The most recent design recommendations for laps are found in fib Model Code 2010 which is likely to influence the next revision of EN-1992. This is of concern to UK industry since laps designed to Model Code 2010 can be significantly longer than laps designed to EN-1992 which UK designers already consider excessive compared with previous UK code requirements. Unlike the previous UK code, BS8110, EN-1992 requires adjacent laps to be offset by 0.3 of the lap length which complicates reinforcement detailing. The paper describes an experimental programme which was undertaken to assess the influence on lap performance of increasing lap length beyond that required for bar yield, shear and staggering of laps. The influence of shear was assessed by comparing the performance of laps of the same length positioned in zones of uniform and varying bending moment. Reinforcement strains were monitored and detailed measurements of crack development and crack widths were obtained with digital image correlation. Results show that very long laps are inefficient with the central half contributing little to force transfer between bars. Shear was found to have no significant influence on lap strength while lapping only 50% of bars at a section increased forces in the lapped bars leading to premature bond failure. Test results are compared with EN-1992 predictions, which are shown to be conservative for the tested laps. Highlights: 18 tests of reinforced concrete beams with tension laps. Very long laps are inefficient with central half contributing little to lap strength. Shear had no significant influence on lap strength. Lapping 50% of bars reduces lap strength compared with 100% laps.